Handbook of research on sustainable development and economics - Thomas, Ken D. 1982- (A volume in the Advances in Finance, Accounting, and Economics (AFAE) Book Series, 2015)
"This book explores topics such as poverty, gender equality, health, security, and the environment through global empirical studies and fundamental frameworks, with the goal of promoting sustainable techniques for the global future"-- Provided by publisher.